Reviews. Jayne Carroll and David N. Parsons (eds.), Perceptions of Place: Twenty-FirstCentury Interpretations of English Place-Name Studies, English Place-Name Society Supernumerary Volume for 2012 (Nottingham: English Place-Name Society, 2013), xxxvi + 474 pp. £35 hardback. ISBN 9780904889864. (2021) - Scott, Maggie
No abstract available